Quantitative assessment of the industrial composition in the country’s regions - Ginevičius, Romualdas; Gedvilaitė, Dainora; Stasiukynas, Andrius (Technological and Economic Development of Economy, 2018)
To this date, insufficient number of reasoned methods for assessing the industrial composition in the country or in the region in an integrated and quantitative manner is on offer. The existing proposals are basically intended for explaining the drivers of change in the industrial composition as well as the reasons thereof. Following this analysis, the most export-oriented industries are determined. Hence, the focus is not on assessing the industrial composition of a country or a region itself in a quantitative manner, but rather the impact of the changes thereof on economic indicators, i.e. derivative measures of industrial composition. The industrial composition of a country or a region can be described through indicators that reflect three key aspects, i.e. the variety of active economic entities by their number, size and types of economic activities. The proposed methodology is suitable for assessing the industrial composition of a country’s region.